2023
DOI: 10.3390/microorganisms12010008
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Autoimmune Neuropsychiatric Disorders Associated with Streptococcal Infections (PANDAS) Syndrome: A 10-Year Retrospective Cohort Study in an Italian Centre of Pediatric Rheumatology

Saverio La Bella,
Marina Attanasi,
Armando Di Ludovico
et al.

Abstract: Background. Pediatric Autoimmune Neuropsychiatric Disorders Associated with Streptococcal Infections (PANDAS) syndrome is a rare pediatric disorder consisting of a sudden onset of obsessive–compulsive disorder (OCD) and/or tics after a group A Streptococcus (GAS) infection. Methods. In the period between 2013 and 2023, 61 children presented to our Pediatric Rheumatology unit with a suspicion of PANDAS syndrome. Among these, a retrospective analysis was conducted, and 19 fulfilled the current classification cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
2
0
0
Order By: Relevance
“…Twenty (83.3%) children had ocular tics, including eyelid blinking, eye rolling, eye widening, and gaze deviation, a result consistent with the report by La Bella et al [28], who found tics involving the eyes in eleven (61%) out of eighteen children with PANDAS. In this subset of patients, we documented significantly higher plasma values of anti-DNase B antibodies (p = 0.05).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Twenty (83.3%) children had ocular tics, including eyelid blinking, eye rolling, eye widening, and gaze deviation, a result consistent with the report by La Bella et al [28], who found tics involving the eyes in eleven (61%) out of eighteen children with PANDAS. In this subset of patients, we documented significantly higher plasma values of anti-DNase B antibodies (p = 0.05).…”
Section: Discussionsupporting
confidence: 89%
“…Boys with PANDAS outnumbered girls by a ratio of 3. [28]. Mean age at onset was 7.25 years, a value similar to those found by the same authors (6.3, 6.4, and 7 years, respectively) [2,5,28] and by Rea et al (6.2 years) [29].…”
Section: Discussionsupporting
confidence: 87%